以「心法」論林兆恩的「世間法」與「出世間法」 = “Xin Fa” as a mean of bridging “Shijian Fa” and “Chushijian Fa” - Ang, Wei Yang (2016)
林兆恩（1517﹣1598）是晚明「三一教」的創教者。他吸收了前人的「三教合一」思想，並將其系統化，進一步ᨀ出了一套獨特的思想體系和工夫論。在某種意義上，林兆恩是「三教合一」思想的集大成者。「三教合一」的基本主張是將儒、佛、道三教合而一之。不同的思想家在處理三教問題都有不同的側䟽，主要的主張有三：「調和」、「會通」與「合一」。目前學術界對於這些概念仍存爭議，但是明確的是，三種主張都有一定程度上的「融合」。其中，「合一」是最高層次的「融合」。有趣的是，儒、佛、道三教之間，存在著種種差異和衝突。最為明顯的是「經世」與「出世」衝突。一般人們都會以「經世」、「出世」二分法，將儒家歸為「經世法」，把佛、道二教歸為「出世法」。兩者之間則處於衝突對立的位置，難以兩者兼顧。既要「合一」就必須解決「經世」、「出世」之衝突。林兆恩承繼了明代的「心學」，發展出「三一教」的「心法」，並從「心法」的角度䟽新定義「經世」與「出世」。其以「心」作為貫通「經世」與「出世」的基礎，使其「三教合一」論合理化。不僅如此，他還進一步發展出了一套具體的工夫論，將「思想理論」落實到「工夫實踐」。本文將梳理林兆恩的「心法」，並探討他如何以「心法」貫通「經世」與「出世」。最後，再以「心法」的「工夫」討論林兆恩在「工夫」上，如何貫通「經世」與「出世」。Lin Chao-en is the founder of “Sanyi Jiao” (三一教) in late Ming dynasty. He inherited the philosophy of the “syncretism of the three teaching” (三教合一) from the preceding thinkers and systemized it to develop an unique system of thoughts and practice. In some sense, he can be regarded as the master of the “syncretism of the three teaching” philosophy. “Syncretism of the three teaching” basically advocates the synthesis of Confucianism, Buddhism and Taoism. Different thinker has different approach when dealing with “syncretism of the three teaching.” The three main approaches are: “Tiaohe” (調和), “Huitong” (會通) and “Heyi” (合一). And the definition of these terms are still greatly argued among modern scholars. However, it is agreeable that there is a certain degree of synthesis in the three different approaches, in which, “Heyi” is definitely the highest form of “synthesis.” It is interesting to note that there are vast differences between Confucianism, Buddhism and Taoism. One obvious difference is the conflict between “Jingshi” and “Chushi.” Generally, scholars would use this dichotomy and segregate the teaching of Confucianism as “Jingshi” and the teaching of Buddhism and Taoism as “Chushi.” They are regarded as opposing and conflicting and there is no way to work both at the same time. Since Lin Chao-en advocates the “syncretism of the three teaching,” he must therefore resolve the conflict of the two. Lin Chao-en inherited the Ming dynasty’s “Xinxue” (心學) and developed the “Xinfa” (心法) of “Sanyi Jiao” and used it to redefine “Jingshi” and “Chushi.” Furthermore, he used “Xin” (心) as a mean to bridge the segregation between “Jingshi” and “Chushi” as well as to rationalize the teaching of “Sanyi Jiao.” He also developed a practice (工夫) to bring his theory into practice. This paper will focus on Lin Chao-en’s “Xinfa” and discuss how it bridges the gap between “Jingshi” and “Chushi,” and finally discuss how it is expressed in his practice.